Herpetofauna of the Pulau Banggi Group of islands off Northeastern Borneo - Das, Indraneil (Society for the Study of Amphibians and Reptiles, 2008)
The limestone islands of the Pulau Banggi (ca. 07º14–19'N, 117º5–10'E) group are situated off the northeast coast of the island of Borneo, and due south of the Philippines islands of Balabac and Palawan (Fig. 1). In geographical terms, they lie between the basins of the South China Sea and that of the Sulu Sea, and cover a total land area of 699 km 2 . Banggi, the largest of these islands, is ca. 700 km 2 The first naturalist recorded to have collected on these islands is Francis Henry Hill Guillemard (1852– 1933), in 1883, on board the 420 ton auxillary screw yacht 'The Marchesa', which visited islands of eastern Asia and New Guinea on a natural history expedition. Although the purpose of the stop at Banggi was to obtain freshwater, Guillemard also made a collection of birds (Chasen and Boden Kloss, 1930). In 1886, in area and has a coastline of 420 km (Teh et al., 2005). Other important islands of the group include Balambangan and Malawali, the former island with extensive limestone formation, with outcrops reaching 120 m (Tuen et al., 2002). Administratively, these islands fall under Kudat District of Sabah (East Malaysia), and are included in the proposed (in 2003) Tun Mustapha Marine Park, designated primarily to protect the rich marine life of the surrounding seas. The archipelago comprises about 70 islands, 33 of which are inhabited by an estimated 80,000 people of various ethnic origins (Biusing, 2001).